Behavior of Listeria monocytogenes in beef Sous vide cooking with Salvia officinalis L. essential oil, during storage at different temperatures. (October 2020) - Moura-Alves, Márcio; Gouveia, Ana R.; de Almeida, José M.M. M.; Monteiro-Silva, Filipe; Silva, José A.; Saraiva, Cristina
Abstract: This study aims to evaluate the effect of Salvia officinalis L. (sage) essential oil (EO) on behavior of L. monocytogenes ATCC679 inoculated in beef processed by Sous-vide cook-chill (SVCC) and stored at 2 or 8 °C during 28 days. Minimum inhibitory concentration (MIC) of L. monocytogenes was obtained with 31.3 μL/mL of EO. D values were determined for samples with EO (21′39″) and without EO (21′17″). Beef samples were inoculated with L. monocytogenes at a concentration of 1 × 108 CFU/mL and vacuum-packed after EO addition at MIC value. Three heat treatments (F) were applied to reduce 1-log10 (F1), 2-log10 (F2) and 3-log10 (F3). EO composition was identified by gas-chromatography mass-spectrometry analysis. The main compounds identified were β-pinene (11.70%), camphor (8.21%), β-thujene (7.82%), 1.8-cineole (5.19%), α-humulene (6.07%) and endoborneol (4.87%).A reduction of approximately 1 log (CFU/g) of L. monocytogenes was observed in EO samples, compared to control samples at 2 °C. At 8 °C, despite exponential development from day 14, lower L. monocytogenes counts were observed in EO samples. Data showed that sage EO can help to control L. monocytogenes growth. However a possibility of using sage as a natural preservative, must be combined with other agents to control microbial growth more effectively. Highlights: Behavior of L. monocytogenes in beef samples differed according to EO or thermic treatment. A high reduction of L. monocytogenes was observed at 2°C in samples with sage EO at the end of storage. The combination of sage EO with heat treatment was only significant in day 2 of storage at 2°C. The effect of heat treatment was only significant úntil day 14 of storage at 8°C.